Operation of an enclosed aquatic ecosystem in the Shenzhou-8 mission - Li, Xiaoyan; Richter, Peter; Hao, Zongjie; An, Yanjun; Wang, Gaohong; Li, Dunhai; Liu, Yongding; Strauch, Sebastian; Schuster, Martin; Haag, Ferdinand; Lebert, Michael (Acta Astronautica, 2017)
Long- term spaceflight needs reliable Biological life support systems (BLSS) to supply astronauts with enough food, fresh air and recycle wasters, but the knowledge about the operation pattern and controlling strategy is rear. For this purpose, a miniaturized enclosed aquatic ecosystem was developed and flown on the Chinese spaceship Shenzhou-8. The system with a total volume of about 60 mL was separated into two chambers by means of a gas transparent membrane. The lower chamber was inoculated with Euglena gracilis cells, and the upper chamber was cultured with Chlorella cells and three snails. After 17.5 days flight, the samples were analyzed. It was found that all snails in the ground module (GM) were alive, while in the flight module (FM) only one snail survived. The total cell numbers, assimilation of nutrients like nitrogen and phosphorus, soluble proteins and carbohydrate contents showed a decrease in FM than in GM. The correlation analysis showed upper chambers of both FM and GM had the same positive and negative correlation factors, while differential correlation was found in lower chambers. These results suggested primary productivity in the enclosed system decreased in microgravity, accompanied with nutrients assimilation. The FM chamber endured lacking of domination species to sustain the system development and GM chamber endured richness in population abundance. These results implied photosynthesis intensity should be reduced to keep the system healthy. More Chlorella but less Euglena might be a useful strategy to sustain system stability. It is the first systematic analysis of enclosed systems in microgravity.
Keywords: Chlorella pyrenoidosa; enclosed aquatic ecosystem; Euglena gracilis; life support system; microgravity; Shenzhou-8